(untitled) (Baghdad Science Journal, 2024)
Deep oxidative desulfurization is a crucial topic for environmental catalysis research for producing a low-sulfur diesel. One of the effective catalysts that have been used recently for oxidative desulfurization of the refractory sulfur compound from model diesel is Keggin-type polyoxometalate. In this work, a Keggin-type catalyst TBAPW11O39, model diesel, Hydrogen peroxide (H2O2) and 1- methy l-3-octyl imidazolium hexafluorophosphate (OMIM(PF6)) were tested under different reaction conditions. The sulfur compound dibenzothiophene (DBT) in model diesel was captured in ionic liquid (IL) and then oxidized to produce related sulfones with H2O2 as an oxidant using TBAPW11O39, in a batch reactor. The impacts of reaction temperature (T)(303,323 and 343)K and time (30-180) min, catalyst dosage 0.5-6 g/l, H2O2/DBT(O/S) molar ratio from 1:1 to 5:1(mole/mole) and IL/oil volume ratio 1/10 – 5/10 (ml/ml) were investigated. The catalyst exhibited high effectiveness for removing DBT using H2O2, with the highest sulfur removal of 96% under the optimum conditions (10 ml of model diesel, T= 343 K, catalyst dosage= 3 g/l, H2O2/DBT = 5:1 (mole: mole) and IL/diesel = 2:10 (ml/ml) for 120 min). These results indicate that the extraction with catalytic oxidation desulfurization using Keggin hybrid catalysts for model diesel fuels is an efficient method and offers promise for achieving ultra-deep desulfurization.